Clinical and echocardiographic factors associated with complications in patients with acute myocardial infarction - Yoandro Rosabal Garcia; Níger Guzman Pérez; Eddy Alberto Rosales Guibert (Universidad de Ciencias Médicas de La Habana, 2023)
Introduction: Acute myocardial infarction is the leading cause of death and disability worldwide, accounting for almost one-third of all deaths and nearly half of non-communicable diseases. Objective: To determine the possible clinical, echocardiographic and therapeutic factors associated with the appearance of complications in acute myocardial infarction. Material and Methods: A retrospective, analytical and observational case-control study was conducted at the Cardiovascular Surgery and Cardiology Center of Santiago de Cuba during the period between 2017 and 2021. The presence of complications in acute myocardial infarction was considered in 137 patients (cases) or not (controls) 411 patients. Results: In the series, there was a predominance of patients under 65 years of age in both study groups, that is, in cases and controls (83.9% and 94.2%, respectively; p = 0.001); males showed the majority of cases (62.4 %), with a       p-value ≤ 0.05. Thrombolytic therapy was not used in the cases and controls (55.5 % and 88.3 %, respectively; p-value ≤ 0.05). Similarly, the ventricular systolic function in both ventricles, the left atrial volume, and parietal motility had a high statistical significance (p-value ≤ 0.05). Conclusions: Clinical and echocardiographic elements such as (age > 65 years, sex, thrombolytic therapy, depressed left ventricular systolic function, elevated left atrium pressure, and altered segmental motility) were associated risk factors for complications in acute myocardial infarction.